Risk factors for intraoperative hemorrhage during cesarean myomectomy - Ji Young Kwon; Ji Hea Byun; Inhye Shin; Subeen Hong; Rayon Kim; In Yang Park (Elsevier, 2021)
Objective: We intended to identify the risk factors of intraoperative hemorrhage on occasions of a combined operation of myomectomy with cesarean section for patients with uterine leiomyoma. Materials and methods: A retrospective cohort study was done of all patients who underwent cesarean myomectomy for intramural leiomyoma at a single university hospital. Cases identified with subserosal leiomyoma, placental disorder, and comorbid conditions related to coagulopathy were excluded. All the included cases were classified into intraoperative hemorrhage and non-hemorrhage group. Obstetric and demographic factors and parameters of leiomyoma were compared between two groups. Results: A total of 302 women underwent cesarean myomectomy during the study period. Among these women, 212 pregnant women met the inclusion criteria. Intraoperative hemorrhage occurred in 43 women (20.3%). There was no significant intergroup difference in the number of removed leiomyomas. Multiple logistic regression analysis demonstrated that lower segmental location (odds ratio [OR], 2.827; 95% confidence interval [CI], 1.033-7.734, P = 0.043) and the diameter (OR, 1.167; 95% CI, 1.044-1.305, P = 0.006) were significant independent risk factors for hemorrhage during cesarean myomectomy. The combination of ≥ 8 cm diameter or lower segmental position of the leiomyoma yielded a specificity of 79.3% for operative hemorrhage during cesarean myomectomy. The negative predictive value of this combination was 88.7% for operative hemorrhage with a prevalence of 20%. Conclusion: The large size and lower segmental position of the leiomyoma are significantly risk factors for intraoperative hemorrhage during cesarean myomectomy. If the leiomyoma is located in the uterine fundus or body and its diameter is less than 8 cm, the removal of leiomyoma may be considered at the time of cesarean section.